2020
DOI: 10.1021/acs.organomet.9b00830
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Iron Acetylides with Carbon Dioxide

Abstract: The acetylido iron hydride trans-[FeH(CCH)(depe) 2 ] reacts with an excess of CO 2 at ambient pressure and temperature to form a five-membered metalalactone cis-[Fe(OC(O)CHCH-κ 2 C,O)(depe) 2 ]. The reaction appears to proceed by electrophilic addition of CO 2 to the β-carbon of the coordinated acetylide and cyclization to form the metalalactone product. At low temperature, a second molecule of CO 2 is incorporated to give a carboxy-substituted metalalactone cis-When the initial metal acetylido hydride is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…Similar observations were also found for the corresponding complexes containing bis(diethylphosphino) ethane as a co-ligand. 77 Similar oxidative coupling transformations, where alkenes are utilised as the AB coupling unit, have been observed across a range of other transition metals. Selected examples are highlighted in Scheme 15.…”
Section: Type 1 Activationmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar observations were also found for the corresponding complexes containing bis(diethylphosphino) ethane as a co-ligand. 77 Similar oxidative coupling transformations, where alkenes are utilised as the AB coupling unit, have been observed across a range of other transition metals. Selected examples are highlighted in Scheme 15.…”
Section: Type 1 Activationmentioning
confidence: 64%
“…Similar observations were also found for the corresponding complexes containing bis(diethylphosphino)ethane as a co-ligand. 77…”
Section: Recent Developments In Metal Ligand Cooperation Methodologie...mentioning
confidence: 99%
“…Additionally, the C(23)–O(1) and C(23)–O(2) bond lengths of 1.291(2) and 1.241(2) indicated partial delocalization of the carboxylate π-bond. Iron metallocycles related to 6 have been previously studied by X-ray diffraction, , though 6 is the first parent lactone derived from CO 2 -ethylene coupling to be structurally characterized.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Field and co-workers described the coupling of CO 2 with various acetylides mediated by low-valent iron dmpe (dmpe = 1,2-bis­(dimethylphosphino)­ethane) and depe (depe = 1,2-bis­(diethylphosphino)­ethane) complexes, in which unsaturated iron lactones were isolated and characterized (Figure ). , While much of the reactivity of the depe and dmpe variants was analogous, important differences in the regioselectivity of the CO 2 coupling were observed with ancillary ligand changes. The dmpe iron complex coupled CO 2 and phenylacetylene to selectively produce an α-substituted unsaturated lactone, while the more sterically hindered depe iron complex produced exclusively β-substituted lactones (Figure ).…”
Section: Introductionmentioning
confidence: 93%
“…The dmpe iron complex coupled CO 2 and phenylacetylene to selectively produce an α-substituted unsaturated lactone, while the more sterically hindered depe iron complex produced exclusively β-substituted lactones (Figure ). Using the depe chelate, our own laboratory has reported that (depe) 2 Fe­(C 2 H 4 ) produces an isolable five-membered saturated metallalactone species via coupling of CO 2 and C 2 H 4 ( A ; Figure ). Upon addition of a proton source, complex A liberates propionic acid .…”
Section: Introductionmentioning
confidence: 99%